Evaluation of color and textural properties of chicken meat momos. Issue 6 (10th November 2014) - Singh, Tanuja; Pathak, Vikas; Verma, Arun; Vincentraju, Rajkumar; Goswami, Meena; Singh, Veer
Abstract : Purpose: – The aim of the present study was to evaluate the textural, color, sensory and microbiological properties of meat momos. Design/methodology/approach: – Three different levels of boiled chopped chicken meat, namely, T1 (45 per cent chicken meat), T2 (50 per cent chicken meat) and T3 (55 per cent chicken meat) were taken as filling material for preparation of meat momos. Findings: – There was no significant difference in lightness (L*), redness (a*) and yellowness (b*) values. The mean hardness, adhesiveness, springiness, cohesiveness, gumminess and chewiness values also differed non significantly. Salmonella and Coliform were not detected in freshly prepared chicken momos. No significant difference was observed for total plate count and the sensory attributes except meat flavor intensity. The overall sensory scores were found to be significantly ( p < 0.05) higher for T2 treatment than other two treatments. Research limitations/implications: – The trials are needed to carry out further study to evaluate storage stability of developed momos. Originality/value: – Meat momos available in the market are not standardized and do not have a defined nutrient content. The standardization and quality evaluation of chicken meat moms can provide the platform for their commercialization at industrial level.